Adolescent patellofemoral pain syndrome: reappraisal of pathophysiology and implications for clinical management - Thierry CONROZIER; Anne LOHSE (Orthopedic Reviews, 2026)
Background Adolescent patellofemoral pain syndrome (APFS) is the most common cause of knee pain in this population. Despite its high prevalence, it remains frequently underestimated and is often considered a benign and self-limiting condition. However, persistent symptoms, significant psychosocial burden, and limited long-term efficacy of conventional treatments challenge this traditional view and call for an updated understanding of its underlying mechanisms and management. Main body This narrative review is based on a structured literature search conducted in PubMed and Google Scholar, with studies selected according to predefined relevance criteria. APFS typically develops around puberty and predominantly affects physically active adolescents, particularly females. Clinical presentation is characterized by activity-related anterior knee pain and pain during prolonged sitting. Diagnosis remains primarily clinical, although it should incorporate assessment of biomechanical, functional, and psychosocial factors. While standard imaging is usually unremarkable, advanced magnetic resonance imaging techniques have revealed early structural and biochemical cartilage alterations. Current evidence supports a multifactorial model of pain involving both peripheral nociceptive sources and central sensitization mechanisms, further supported by neuroimaging studies. Psychosocial factors, including kinesiophobia, reduced participation in physical activity, and impaired quality of life, play a key role in symptom persistence. Standard management based on education, load management, and rehabilitation yields suboptimal outcomes in a substantial proportion of adolescents. Emerging approaches include psychologically informed interventions, digital adherence strategies, and adjunctive therapies such as intra-articular hyaluronic acid. Conclusion APFS should no longer be regarded as a benign condition. A shift toward earlier, multimodal, and individualized management is warranted, integrating physical, psychological, and educational components. Improved understanding of central pain mechanisms and the development of adjunctive therapeutic strategies may contribute to better outcomes and prevention of chronicity.